Elimination of Infectious Diseases from the South-East Asia Region Keeping the Promise - Singh, Poonam Khetrapal (SpringerBriefs in Public Health, 2021)
This book discusses the historical context, country experience, and best practices that led to eliminating infectious diseases from the WHO's South-East Asia Region, such as malaria, lymphatic filariasis, yaws, trachoma, and mother-to-child HIV in the mid-twentieth and twenty-first century. The UN Sustainable Development Goals (3.3) targets to end AIDS, tuberculosis, malaria, and neglected tropical diseases and combat hepatitis, water-borne diseases and other communicable diseases by 2030. In this context, this book is of high significance to countries from the SEA region and around the globe. It helps create national strategies and action plans on infectious disease elimination and thus attaining SDG 3.3. This is an open access book.